Growth and yield response of shallots to NPK, NK, and humic acid under different mycorrhiza application - Laila, Alfu; Sulistyorini, Endang (Kultivasi, 2026)
One strategy to increase shallot production is the utilization of microorganisms in the soil, such as arbuscular mycorrhizal fungi (AMF), which is applied together with fertilizer. This research aimed to investigate the effects of different nutrient inputs and mycorrhizal association on the growth and yield of shallots. This study used a split-plot design with three replications as blocks. The main plot included four treatments: no nutrient inputs, NPK fertilizer, NK fertilizer, and humic acid, while the subplot involved the mycorrhiza application (with or without). The measured variables included growth (plant height and number of leaves) and yield (fresh weight and number of bulbs per plant). The results showed no interaction between treatments for any growth or yield parameters. Application of humic acid significantly improved shallot development and yield, producing the highest results compared to other fertilizer types. Mycorrhizal inoculation enhanced plant height and boosted bulb weight per plant. The application of humic substances has been proven to increase 27.82%, while AMF enhanced 12.9 % weight bulb of shallots. Hence, humic substances have the potential to enhance the shallot with or without AMF application.